Promotion Mix Of E-Catalog at Deputy Coordination Of Regional Development And Spatial Planning, Coordinating Ministry For Economic Affairs - Tintin Sri Murtinah; Ritma Wijayanti (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
Deputy Coordination of Regional Development and Spatial Planning was a part of unit in Coordinating Ministry for Economic Affairs. Implementation of Procurement of Goods/Services to Deputy Coordination of Regional Development and Spatial Planning through E-Catalogs is still not optimal. This study aims to determine Promotion Mix of E-Catalog at Deputy Coordination of Regional Development and Spatial Planning, Coordinating Ministry for Economic Affairs. This research was conducted using a descriptive method with a qualitative approach. Data collection techniques were carried out by documents review and interviews. Data analysis was carried out by matching data from document reviews and interviews to describe the results of the research. Based on the three aspects measured, namely the sales promotion aspect, the publicity aspect, and the personal selling aspect which shows that Promotion Mix of E-Catalog at Deputy Coordination of Regional Development and Spatial Planning, Coordinating Ministry for Economic Affairs, has not gone well yet. The results of interviews and document review concluded that: first, the price offered in the E-Catalog tends to be higher than the direct procurement process. Second, the items contained in the E-Catalog were incomplete and the information contained in the E-Catalog was still difficult to understand. Third, the menus in the E-Catalog were still unfamiliar so they were not user friendly. As an effort to optimize the promotion mix at E-Catalog to the Deputy for Coordination of Regional Development and Spatial Planning, the Coordinating Ministry for Economic Affairs, the author suggested several things as follows: Carry out the procurement of commodities/services at the beginning ; Be more selective in determining the specifications of commodities/services, especially if the price offered on the E-Catalog is more expensive; Complete the existing processes in the E-Catalog to completion; Understand the information contained in the E-Catalog; Be more selective in finding the commodities according to the required specifications; Adapt to implement the procurement of commodities/services through ecatalogs; Increase the office bandwidth capacity.